The average speed from six minutes walk test as a parameter to determine the training load for physical reconditioning of chronic pulmonary disease patients - Figueiredo, Pedro Henrique Scheidt; Guimarães, Fernando Silva (Acta Fisiátrica, 2009)
The purpose of this study was to evaluate the effectiveness of an aerobic reconditioning protocol to improve functional capacity and dyspnea of chronic pulmonary disease patients, based on the six-minute walk test (6MWD) for determining the load of training. Methodology: were selected 10 chronic pulmonary disease patients (9 M, 1 F) with average age of 61.5 ± 10.6 years, presenting clinical stability and without contraindications to the practice of aerobic exercise. The protocol was conducted in a treadmill, with 3 sessions per week, for along 8 weeks. The treadmill walking speed was set at 85% of average speed obtained from the 6MWD. Functional capacity and dyspnea were evaluated at the beginning and at the end of training. For statistical analysis were used paired t-test and Wilcoxon according to the variables characteristics. Differences were considered statistically significant when p < 0.05. Results: It was observed improves in functional capacity by increased distance on 6MWD (mean = 445.7 ± 175 m vs 565.8 ± 174 m, p <0.01) as well as reducing dyspnea by MMRC [median = 3 (2 - 4) vs 1 (0-3), p <0.05]. Conclusion: The 6MWD average speed is an effective parameter for determining the training load in aerobic reconditioning programs for pulmonary disease patients.